REINFORCEMENT OF FAMILY SUPPORT TO OVERCOME RELIGIOUS DISCRIMINATION IN IBTIHAJ MUHAMMAD AND S.K. ALI’S THE PROUDEST BLUE - Nurwahidah, Desti; Daulay, Resneri (Rubikon : Journal of Transnational American Studies, 2025)
The present study analyses family and support systems in addressing religious discrimination, focusing specifically on Islamophobic incidents portrayed in Ibtihaj Muhammad's children's picture book The Proudest Blue. Using Kimberlé Crenshaw's intersectionality theory and Talcott Parsons' functionalism, this research examines how religious discrimination manifests in educational settings and how various environmental support mechanisms respond to these challenges. Through the application of a qualitative research method, focusing on textual and visual elements, the study identifies specific instances of Islamophobic behavior, cultural misunderstanding, and social othering. In addition, it explores strategies employed by families in the face of challenges, peer relationships within these communities, and the responses of the community at large. The findings reveal that Asiya experiences religious discrimination rather than generalized racism, with incidents specifically targeting Islamic practices through the degradation of religious symbols. The analysis demonstrates that successful social integration occurs through adaptive processes that allow Muslim students to participate fully in educational communities while maintaining their faith practices. This study contributes to the understanding of the potential of children's literature to shed light on the challenges posed by religious discrimination, as well as the intricate nature of supportive environments within educational settings.